PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH BERBASIS STRATEGI SHUFFLE AND RECALL UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF SISWA PADA KONSEP GEOGRAFI DI SMA - Nurliah Nurliah; Uca Uca; Sukri Nyompa; Maddatuang Maddatuang; Hasriyanti Hasriyanti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to improve students’ understanding of geographical concepts at SMA Negeri 1 Menui Kepulauan through the implementation of the Make a Match learning model based on the Shuffle and Recall strategy. The main problem addressed in this study is the low level of students’ learning mastery (below 75), which is caused by the dominance of conventional teaching methods and limited student engagement in understanding complex concepts. The research method employed was Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were students of class XI Habibi and XI Maxweber. The results indicate a significant improvement in students’ conceptual understanding in both classes. In class XI Habibi, the remembering aspect (C1) increased by 9%, understanding (C2) by 21%, and applying (C3) by 20%. Meanwhile, in class XI Maxweber, improvements were observed in C1 by 14%, C2 by 24%, and C3 by 24%. Obstacles such as classroom management issues in Cycle I were successfully addressed in Cycle II through clearer instructions. In conclusion, the Make a Match learning model based on the Shuffle and Recall strategy is effective in creating active and enjoyable learning environments while maximizing students’ memory and understanding of geographical concepts